Computer-Based Training Programs for Older People with Mild Cognitive Impairment and/or Dementia - Klimova, Blanka; Maresova, Petra (Frontiers in Human Neuroscience, 2017)
Currently, due to the demographic trends, the number of aging population groups is dramatically rising, especially in developed countries. This trend causes serious economic and social issues, but also an increase of aging disorders such as mild cognitive impairment (MCI) or dementia in older population groups. MCI and dementia are connected with deterioration of cognitive functions. The aim of this mini review is therefore to explore whether computer-based training programs might be an effective intervention tool for older people with MCI and/or dementia or not. The methods include a literature search in the world’s acknowledged databases: Web of Science, Scopus, Science Direct, MEDLINE, and Springer, and consequently, evaluation of the findings of the relevant studies. The findings from the selected studies are quite neutral with respect to the efficacy of the computer assisted intervention programs on the improvement of basic cognitive functions. On the one hand, they suggest that the computer-based training interventions might generate some positive effects on patients with MCI and/or dementia, such as the improvement of learning and short-term memory, as well as behavioral symptoms. On the other hand, these training interventions seem to be short-term, with small sample sizes, and their efficacy was proved only in the half of the detected studies. Therefore more longitudinal randomized controlled trials are needed to prove the efficacy of the computer-based training programs among older individuals with mild cognitive impairment and/or dementia.